PENGARUH MODEL PEMBELAJARAN GROUP INVESTIGATION (GI) DENGAN MEMANFAATKAN LINGKUNGAN SEKOLAH SEBAGAI LINGKUNGAN BELAJAR TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK DI SMAN 12 KUPANG - Maria Ingrawati Amol; Agustinus Hale Manek; Mikael Samin (Universitas Nusa Cendana, 2026)
Modern education requires students to possess critical thinking skills to respond to social and environmental challenges. One innovative learning approach that supports this goal is the Group Investigation (GI) model integrated with the school environment as a learning resource. This study aimed to determine the effect of the Group Investigation model on students’ critical thinking skills in the topic of environment and its problems at SMA Negeri 12 Kupang. The research employed a quantitative approach with a quasi-experimental design. Data were collected through critical thinking tests administered as pretests and posttests and analyzed using normality, homogeneity, and Independent Sample t-tests. The GI model was implemented through six stages: topic selection, cooperative planning, investigation, analysis and synthesis, presentation of findings, and evaluation. The results showed that the experimental class achieved a higher average posttest score (82,86) than the control class (70,82). The significance value of 0,000 (< 0,05) indicates that the Group Investigation model effectively improves students’ critical thinking skills.